Campo e palavras: dimensões da Questão Agrária no Ceará, 1954-1964 - Souza, Enilce Lima Cavalcante de (2005)
The present study aims at discussing some dimensions of the Agrarian Question in Ceará, between 1954 and 1964. At the beginning, we analyze the debates about the agrarian legislation, land concentration, migration and violence, through Fortal eza newspapers. This research also looks into the social communication ways towards the peasant struggle, trough Terra Livre newspaper, as memory and document that allows an inventory of peasant struggle in Ceará. We demonstrate that its articles allows us to learn many debates levels, in that context, between the 40’s middles and the 60’s beginning as well as some dimensions of peasant culture and militants memories.